A Comparative Study of Generative AI Tutors and Traditional Education: Evaluating Risks and Benefits for Postgraduate Learning at Riphah International University - Hijab Zahra; Sameen Aqeel; Kisaa Zahra; Sidra Lateef Shah; Babar Khan (Social Science Review Archives, 2025)
Generative AI tutors, like ChatGPT, with traditional teaching at Riphah International University. Its expressions at how both approaches benefit postgraduate students in their education. The exploration demonstrates that AI tutors save time, give immediate response, and make learning extra flexible. Though, they can also give incorrect or frequent responses and absence emotional support. Traditional teaching aids students recognize better through teacher supervision, face-to-face communication, and inspiration, but it can be slower and less flexible. A assessment of MPhil students initiate that most liked AI tools for their comfort and effectiveness, though many still cherished traditional instruction for deeper understanding. The study accomplishes that the best consequences come when AI and teachers work calm, as AI should provision learning but not replace teachers.